Modern tools in the management of competitiveness of innovative entrepreneurship - K. Reshetov (Модернизация, инновация, развитие, 2016)
The purpose of this paper is to study the role of planning and forecasting in management of economic systems, including the management of innovative business structures. Methods. Methodological basis of this paper is generalization of literary sources.Results. The article shows the importance and feasibility of using modern tools in the management of competitiveness of innovative entrepreneurship, in particular the need to apply foresight design and road mapping. This article substantiates the practical necessity of using modern innovative business structures in order to achieve high competitiveness planning tools and forecasting of its activities (and in particular, foresight design and road mapping).